2016
DOI: 10.1111/jop.12485
|View full text |Cite
|
Sign up to set email alerts
|

LAMC2 is a predictive marker for the malignant progression of leukoplakia

Abstract: The results of this study highlight the value of LAMC2 as a marker of cancer invasion. LAMC2-positive foci in leukoplakia suggest an imminent risk of cancer. LAMC2 immunostaining is expected to contribute to a more precise assessment of the malignancy of leukoplakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Afterward, the anti‐tumor effects of miR‐765 and the oncogene role of LAMC2 were confirmed via CCK8, colony formation, and transwell assay. It has been widely reported as an oncogene and contributes to malignant progression and metastasis in several cancers . Silencing of LAMC2 was proved to significantly inhibit cell migration and invasion in HNSCC cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the anti‐tumor effects of miR‐765 and the oncogene role of LAMC2 were confirmed via CCK8, colony formation, and transwell assay. It has been widely reported as an oncogene and contributes to malignant progression and metastasis in several cancers . Silencing of LAMC2 was proved to significantly inhibit cell migration and invasion in HNSCC cells .…”
Section: Discussionmentioning
confidence: 99%
“…LAMC2 is a subunit of the heterotrimeric glycoprotein laminin‐332, consisting of the α3, β3, and γ2 chains and located on chromosome 1q25‐q31. Overexpression of LAMC2 is regarded as a predictive marker for the poor prognosis and metastatic potential of colorectal cancer, leukoplakia, and lung adenocarcinoma …”
Section: Introductionmentioning
confidence: 99%
“…LAMC2 is a subunit of the heterotrimeric glycoprotein laminin‐332, consisting of the α3, β3 and ϒ2 chains; its coding gene is located on chromosome 1q25‐q31. Overexpression of LAMC2 has been demonstrated at the OSCC cancer‐stromal interface, and IHC studies in leukoplakia found that LAMC2‐positive foci were a significant predictive factor for malignant progression of leukoplakia, suggesting an imminent risk of cancer (Nguyen et al, ). Complementary base pairs for binding between miR‐765 and LINC00511 and between miR‐765 and LAMC2 mRNA were predicted in silico, thus identifying potential “target regions.” In vitro studies indicated that LINC00511 could regulate the expression of LAMC2 through sponging miR‐765 and also highlighted in Tca‐8113 cells that downregulation of LINC00511 significantly inhibited cell proliferation, impeded the colony formation ability and suppressed cell invasion capacity according to the invasion assay.…”
Section: The Endogenous Rna Networkmentioning
confidence: 99%
“…LAMC2 is a subunit of the heterotrimeric glycoprotein laminin-332, consisting of the α3, β3 and ϒ2 chains; its coding gene is located on chromosome 1q25-q31. Overexpression of LAMC2 has been demonstrated at the OSCC cancer-stromal interface, and IHC studies in leukoplakia found that LAMC2-positive foci w ere a significant predictive factor for malignant progression of leu koplakia, suggesting an imminent risk of cancer (Nguyen et al, 2017). Complementary base pairs for binding between miR-765 and LI NC00511 and between miR-765 and LAMC2 mRNA were predic ted in silico, thus identifying potential "target regions."…”
Section: Linc00511mentioning
confidence: 99%
“…Fifty one spots were fully evaluable after the loss of spots due to multiple sectioning. Histological evaluation was done as previously described [15]. Cancer-associated inflammation was scored based on the density of inflammatory cell infiltrates around tumor nests at the invasion front.…”
Section: Oscc Tissue Specimens and Immunohistochemistrymentioning
confidence: 99%